Indoor man: notes on masculinity and neoliberalism. (2nd July 2016) - Bazzano, Manu
Abstract : This article reflects on contemporary notions of masculinity in relation to sexuality, the internet and the latest addendum to the neoliberal project, the 'pharmaco-pornographic' management of affect. Drawing on clinical work, on Nietzschean notions of culture and civilization and on contemporary critical theory, the author asks whether psychotherapy can help contemporary men out of the impasse between wildness and domestication. To this purpose, the article also sketches the basis for a feral philosophy that may be able to navigate a middle path for a masculine identity that is stuck between brutality and docility.